Treatment of recurrent acute tonsillitis—a systematic review and clinical practice recommendations - Guntinas-Lichius, Orlando; Geißler, Katharina; Mäkitie, Antti A.; Ronen, Ohad; Bradley, Patrick J.; Rinaldo, Alessandra; Takes, Robert P.; Ferlito, Alfio (Frontiers in Surgery, 2023)
There is an ongoing debate on indications for tonsil surgery in both children and adults with recurrent acute tonsillitis. The aim is to provide practical recommendations for diagnostics and treatment for recurrent acute tonsillitis including evidence-based decision making for tonsillectomy.A systematic literature search in PubMed, Embase, Web of Science, and ScienceDirect from 2014 until April 2023 resulted in 68 articles. These were the basis for the review and a comprehensive series of consensus statements on the most important diagnostics and indications for both non-surgical and surgical therapy. A consensus paper circulated among the authors and members of the International Head and Neck Scientific Group until a final agreement was reached for all recommendations.Results: A differentiation between sore throat and tonsillitis patient episodes is mostly not feasible, hence not relevant for diagnostic decision making. Diagnostics of a tonsillitis/sore throat episode should always include a classification with a scoring system (Centor, McIssac, FeverPain score) to estimate the probability of a bacterial tonsillitis, mainly due to group A streptococcus (GAS). In ambiguous cases, a point-of-care test (POCT) GAS swab test is helpful. Consecutive counting of the tonsillitis/sore throat episodes is important. In addition, a specific quality of life score (Tonsillectomy Outcome Inventory 14 or Tonsil and Adenoid Health Status Instrument) should be used for each episode. Conservative treatment includes a combination of paracetamol and/or non-steroidal anti-inflammatory drugs (NSAID). In case of high probability of bacterial tonsillitis, but only in such cases, and especially in risk patients, standard antibiotic treatment is initiated directly or by delayed prescription.Tonsillectomy is indicated and highly effective if the patient has had ≥7 adequately treated episodes in the preceding year, or ≥5 such episodes in each of the preceding two years, or ≥3 4 such episodes in each of the preceding three years. Essential part of surgery is a standardized pain management because severe postoperative pain can be expected in most patients.It is possible to follow a stringent treatment algorithm for an optimal and evidence-based treatment of patients with recurrent acute tonsillitis. This will help to decrease the worldwide treatment variability, antibiotic overuse, and avoid ineffective tonsillectomy.